2022
DOI: 10.1021/acs.langmuir.2c01557
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sterilization on the Colloidal Stability of Ligand-Free Gold Nanoparticles for Biomedical Applications

Abstract: Sterilization is a major prerequisite for the utilization of nanoparticle colloids in biomedicine, a process well examined for particles derived from chemical synthesis although highly underexplored for electrostatically stabilized ligand-free gold nanoparticles (AuNPs). Hence, in this work, we comprehensively examined and compared the physicochemical characteristics of laser-generated ligand-free colloidal AuNPs exposed to steam sterilization and sterile filtration as a function of particle size and mass conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…This trend suggests that particles contain multiple crystallite domains. In all solvents, the nanoZIF-8 particles exhibit large and stable zeta potentials, as consistent with DLVO theory that colloids are stabilized by charged surface layers that repel neighboring particles and prevent aggregation. Although ZIF-8 particles have been reported to degrade gradually in water, these studies also suggested a strong concentration dependence where more dilute solution degraded faster, whereas the saturated solutions studied were prepared at far higher concentrations. Furthermore, these nanoZIF-8 methanolic suspensions display visual stability for at least one-month storage, requiring only gentle sonication (∼10 min.)…”
Section: Resultssupporting
confidence: 76%
“…This trend suggests that particles contain multiple crystallite domains. In all solvents, the nanoZIF-8 particles exhibit large and stable zeta potentials, as consistent with DLVO theory that colloids are stabilized by charged surface layers that repel neighboring particles and prevent aggregation. Although ZIF-8 particles have been reported to degrade gradually in water, these studies also suggested a strong concentration dependence where more dilute solution degraded faster, whereas the saturated solutions studied were prepared at far higher concentrations. Furthermore, these nanoZIF-8 methanolic suspensions display visual stability for at least one-month storage, requiring only gentle sonication (∼10 min.)…”
Section: Resultssupporting
confidence: 76%
“…The observed trends of the single particle mass normalized energy deposition outside the particle from the MC simulations [10] is in good accordance with our observations where ROS generated in the presence of 5 and 10 nm particles is higher than in larger AuNP (Figure 5), even though a comparison between single particle MC simulations normalized by particle mass and ensemble measurements normalized by surface area should not be overinterpreted. Next to physical effects, it is also well known that surface chemistry and catalytic activity of surface atoms contributes to ROS formation upon proton irradiation [5c,6,17] . It is worth mentioning here that Zwiehoff et al.…”
Section: Resultsmentioning
confidence: 91%
“…[3g,16] The long-term colloidal stability of size controlled laser-fabricated AuNPs as well as their compatibility with common sterilization methods has been recently demonstrated. [17] When laser-generated AuNPs are used in proton therapy, the NPs surfaces are in direct contact with the surrounding liquid, which might maximize the ROS formation efficiency due to the absence of radical scavenging effect of organic surfactants. In a recent study, Zwiehoff et al identified that the NP-assisted enhancement in proton therapy of PtNPs is mainly driven by the number of surface atoms and not by particle mass or particle size, while a comparison between Pt and AuNPs also indicated a substantial influence of the chemical activity of the surface atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] This is highly relevant as the surface of the NP has been identified to be the active part of the sensitizing effect. [15,16,31] Consequently, strong effects of these proteins on the catalytic activity of the NP in water splitting and radical generation are expected. Serum albumin (SA) is a main component of the blood serum [32] .…”
Section: Introductionmentioning
confidence: 99%